Development Of Dna Aptamer Against Envelope 2 Protein Of Chikungunya Virus And Their Diagnostic Potentiality - Andrew, Anna (2024)
Chikungunya virus (CHIKV) infections are mosquito-borne viral infections that are always underreported and misdiagnosed as other virus infections. Antigen detection tests can detect CHIKV in acute-phase samples but are beleaguered by issues associated with antibodies that are sensitive to temperatures, expensive and prone to batch variations. As an alternative to antibodies, aptamers are cheaper and have no batch-to-batch variation. This study aims to isolate aptamers that can be used to develop diagnostic tests for CHIKV